2009
DOI: 10.1080/01904160903392659
|View full text |Cite
|
Sign up to set email alerts
|

High Fertilizer Rates Increase Susceptibility of Tea to Water Stress

Abstract: 2 A study to determine the association of fertilizer with soil water deficit in tea [Camellia sinensis (L.) O. Kuntze] was conducted in a rain-out shelter using potted plants, in which five rates of fertilizer (0, 75, 150, 225 and 300 kg Nitrogen ha −1 ) and six levels of soil water content (38, 34, 30, 26, 22 and 18% v/v) were applied in a complete randomized design and replicated three times. The soil water treatment was maintained for a period of 12 weeks during which shoot growth, plant water relations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 26 publications
3
31
0
1
Order By: Relevance
“…Approximately 260,000 hectares of tea plantations in Yunnan province China were harmed by continuous drought in the spring of 2010 (Liu and Chen, 2014). It was reported that DS affected tea production by 14-33%, with nearly 6-19% plant mortality (Cheruiyot et al, 2010). As previously reported, tea plants adapt to resist DS through regulation of photosynthesis and osmosis as well as scavenging ROS (Guo et al, 2009;Upadhyaya and Panda, 2004).…”
Section: Introductionmentioning
confidence: 76%
“…Approximately 260,000 hectares of tea plantations in Yunnan province China were harmed by continuous drought in the spring of 2010 (Liu and Chen, 2014). It was reported that DS affected tea production by 14-33%, with nearly 6-19% plant mortality (Cheruiyot et al, 2010). As previously reported, tea plants adapt to resist DS through regulation of photosynthesis and osmosis as well as scavenging ROS (Guo et al, 2009;Upadhyaya and Panda, 2004).…”
Section: Introductionmentioning
confidence: 76%
“…The tea plant (Camellia sinensis) is one of the most popular beverage crops worldwide, but its growth and productivity are adversely affected by DS. Drought was reported not only to lead to a 14-33% reduction in tea production but also to cause 6-19% plant mortality (Cheruiyot et al 2009). A limited number of tea miRNAs have been identified using high-throughput deep sequencing and bioinformatics approaches (Das and Mondal 2010, Jeyaraj et al 2014, Zhu and Luo 2013, Zhang et al 2014b, Zheng et al 2015, but drought-responsive miRNAs have not been globally identified in tea plants.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that high application rates of N fertilizer raise the optimal soil water content required by tea plants and subsequently lower tea productivity and survival during drought (Cheruiyot et al 2009). A rate of N fertilizer application above 200 kg ha -1 limits the growth and yield of tea during a drought season (Ng'etich 1999).…”
Section: Effect Of Fertilizer On Induction Of Drought Stressmentioning
confidence: 99%
“…A rate of N fertilizer application above 200 kg ha -1 limits the growth and yield of tea during a drought season (Ng'etich 1999). The lack of tolerance to water stress in well-fertilized tea plants is mainly due to the modification of assimilate partitioning leading to an increased leaf-to-root mass ratio as well as to a reduction in soil-plant hydraulic conductivity (Cheruiyot et al 2009). …”
Section: Effect Of Fertilizer On Induction Of Drought Stressmentioning
confidence: 99%